Effect of non-fluoride agents on the prevention of dental caries in primary dentition: A systematic review. - Yu Wang; Jialing Li; Weibin Sun; Huang Li; Richard D Cannon; Li Mei (PLoS ONE, 2017)
Objective To assess the effect of non-fluoride agents on the prevention of dental caries in primary dentition. Materials and methods Medline, Web of Science, Embase, Cochrane Library, CBM and CNKI databases were searched to identify all the relevant articles published prior to 16 December 2016. Grey literature was also searched. Randomized controlled human clinical trials in which non-fluoride agents were delivered by any method were considered. Results Of the 1,236 studies screened, 39 full articles were scrutinized and 14 selected for inclusion in the final sample. Five chemical agents, namely arginine, casein phosphopeptide-amorphous calcium phosphate (CPP-ACP), chlorhexidine, triclosan and xylitol were investigated in these included studies. The cariostatic effects of non-fluoride agents in vivo were evaluated in comparison with fluoride or placebos in randomized controlled trials. There is evidence that the use of certain doses of xylitol may be effective in arresting dental caries in primary dentition. However, quantitative synthesis could not be carried out because of the clinical and methodological heterogeneity of the included studies. Conclusions A study at low risk of bias indicated that daily use of xylitol wipes is a useful adjunct for caries control in young children, however, this conclusion should be interpreted with caution as this study had a very limited sample size. Chlorhexidine and CPP-ACP may be more effective than a placebo in managing caries in primary dentition, but their effectiveness is borderline when compared with fluoride. Arginine-containing mint confection and 0.3% triclosan varnish were found to reduce caries development in primary teeth but the evidence was at high risk of bias. High quality randomized controlled trials are needed in order to make a conclusive recommendation.